Lessons learned and challenges ahead for the WTO Trade Monitoring exercise - Peter Bogetoft Pedersen; Antonia Diakantoni (World Trade Organization (WTO), 2020)
A little over a decade has passed since the onset of the global financial crisis in 2008. Shortly after the collapse of the Lehman Brothers investment bank, an internal Secretariat Task Force was established by the WTO Director-General to monitor the trade-related developments associated with the crisis. Meeting in London in early 2009, the G20 Leaders mandated the WTO, together with other international bodies, to monitor and report publicly on G20 adherence to resisting protectionism and promoting global trade and investment. Since then, 22 G20 reports and 24 WTO-wide reports have been published. The paper will introduce the WTO Trade Monitoring exercise. It will show how the idea and the principles behind the current Trade Monitoring effort have much earlier origins than the financial crisis. It will also provide an overview of selected trends and developments identified by the monitoring exercise since 2009 and will focus on recent developments in the global trading environment, including the effects of the increasingly protectionist rhetoric which has characterized much of the debate on trade over the past couple of years. Finally, the paper will address the challenges facing the WTO monitoring exercise, and the way forward after ten years of existence.
Keywords: F13; F14; F61; 330; trade monitoring; protectionism; trade restrictions; trade facilitation